Rice CO 53: A high yielding drought tolerant rice variety for drought prone districts of Tamil Nadu - S. Robin, P. Jeyaprakash, R. Pushpam*, K. Amudha, R. Saraswathi, K. Ganesamurthy, S. Muthuramu, P. Yogameenakshi, R. Arulmozhi, S. Radhamani, V. Ravichandran, S. Suresh, A. Ramanathan, R. P. Soundararajan, V. Balasubramani, C. Gopalakrishnan, K. Krishnasurender, G. Senthil Kumar and S.Geetha (Electronic Journal of Plant Breeding, 2022)
Early duration drought tolerant rice culture CB 06803, a derivative of the cross PMK (R ) 3 x Norungan was released as Rice CO 53 during the year 2020 as an alternate variety for Anna(R)4, with 115 -120 days duration. It possesses desirable features like high yield, drought tolerance and better physiological efficiency. This culture with semi dwarf stature has efficient tillering capacity, long droopy panicles with a highly acceptable plant characters and is a replacement for the rice variety Anna (R) 4 due to its grain yield and pest and disease resistance. In the overall yield analysis, the culture CB06803 recorded an overall mean grain yield of 3718 kg/ha which was 12.19 per cent increase over TKM (R) 12 and 14.08 per cent over Anna (R) 4 under dry condition. Under semi dry condition, it recorded 3866 kg/ha with 18.40 per cent increase over TKM (R) 12 and 8.67 per cent over Anna (R) 4. It is moderately resistant to WBPH, leaf blast, neck blast, sheath rot, brown spot and RTD under artificial condition. It has white short bold rice with high milling percentage (69.6), head rice recovery (59.6%) and suitable for idly making. The culture, CB 06803 had better agronomic efficiency than TKM (R)12 and Anna (R) 4 by recording more number of productive tillers per plant and grain yield under control and drought. The culture CB 06803 had better physiological efficiency under drought than TKM (R) 12 and Anna (R) 4 having higher RWC, total chlorophyll content, chlorophyll stability index, photosynthetic rate, stomatal conductance and photo chemical efficiency. The culture had higher proline content than TKM (R) 12 and was on par with Anna (R) 4. It had higher catalase activity than Anna (R) 4. CB 06803 had better physiological efficiency under drought by showing partial closure of stomata as that of Sahbagidhan. CO 53 with higher grain yield under drought, disease resistance and short bold grains and suitable for cultivation in drought prone districts of Tamil Nadu as direct seeded rainfed or semi dry rice ecosystem.